Penerapan E-Book Kibashi pada Pembelajaran Pendidikan Agama Islam di SDN Rancamulya Kelas 5 - Khoirunnisa, Aliya; Niar, Siti Aisyah; Nabila, Cindy Tia; Aeni, Ani Nur (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research is motivated by the importance of using learning media in the learning process. Researchers use an e-book called